Space distribution of EEG responses to hanoi-moving visual and auditory stimulation with Fourier Independent Component Analysis - Li, Shijun; Wang, Yi; Bin, Guangyu; Huang, Xiaoshan; Zhang, Dan; Liu, Gang; Lv, Yanwei; Gao, Xiaorong; Gao, Shangkai; Ma, Lin (Frontiers in Human Neuroscience, 2015)
Background and objective: The relationship between EEG source signals and action-related visual and auditory stimulation is still not well understood. The objective of this study was to identify EEG source signals and their associated action-related visual and auditory responses, especially independent components of EEG. Methods: A hand-moving-Hanoi video paradigm was used to study neural correlates of the action-related visual and auditory information processing determined by mu rhythm (8-12 Hz) in 16 healthy young subjects. Independent component analysis (ICA) was applied to identify separate EEG sources, and further computed in the frequency domain by applying-Fourier transform ICA (F-ICA). Results: F-ICA found more sensory stimuli-related independent components located within the sensorimotor region than ICA did. The total number of independent components of interest from F-ICA was 768, twice that of 384 from traditional time-domain ICA (p<0.05). In the sensory-motor region C3 or C4, the total source signals intensity distribution values from all 14 subjects was 23.00 (Mean1.64±1.17) from F-ICA; which was more than the 10.5 (Mean 0.75±0.62) from traditional time-domain ICA (p<0.05). Furthermore, the intensity distribution of source signals in the C3 or C4 region was statistically significant between the ICA and F-ICA groups (strong 50% versus 92%; weak 50% versus 8% retrospectively; p<0.05). In the Pz region, the total source signal intensity distribution from F-ICA was 12.50 (Mean 0.89±0.53); although exceeding that of traditional time-domain ICA 8.20 (Mean 0.59±0.48), the difference wasn't statistically significant (p>0.05). Conclusions: These results support the hypothesis that mu rhythm was sensitive to detection of the cognitive expression, which could be reflected by the function in the parietal lobe sensory-motor region. The results of this study could potentially be applied into early diagnosis for those with visual and hearing impairments in the future.